Failure of calcium gluconate internal gelation for prolonging drug release from alginate–chitosanbased ocular insert of atenolol (Journal of Pharmaceutical Negative Results, 2010)
Background: The aim of the investigation was to develop and evaluate ocular polymericfilm of atenolol for the management of glaucoma. Materials and Methods: Fixedconcentration blends of sodium alginate (NaAlg) and chitosan were combined with thevarying concentration of calcium gluconate and the resulting hydrogels were casted asocular films. Various physicochemical studies and in vitro release tests of the preparedfilms were carried out to study the effect of calcium gluconate addition to alginate–chitosan blend films. Results: Cumulative % drug released from the formulationsranged from 95 to 99% within 5- to 12-hour period. The drug release enhanced withincorporation of higher ratios of calcium gluconate. F1 (2% NaAlg and 1% chitosanwithout calcium gluconate) sustained the drug release for the longest period of time (12hours). Addition of calcium gluconate to the formulation resulted in faster drug releaserather than sustained drug release. Conclusion: The results showed that the additionof calcium gluconate leads to a change in the release capacities of the matrices. Despitethe presence of calcium ions and thus the possibility of an ionic interaction, the internalgelation of the polymer matrix lead to enhanced drug release and poor sustaining ofdrug. The sustained release effect of NaAlg–chitosan matrices alone was the best amongthe formulations studied.